Profil Pelayanan Resep dengan Obat Glibenklamid di RSUD Muyang kute Bener Meriah - Masriani; Razoki, Razoki; Astriani Natalia Br Ginting (Yayasan Penelitian dan Inovasi Sumatera, 2025)
Background: Optimal pharmaceutical services are essential in chronic disease management, particularly in diabetes mellitus, where glibenclamide is frequently prescribed. Inadequate dispensing practices and lack of patient information can compromise treatment outcomes. Objective: This study aimed to evaluate the profile of prescription services involving glibenclamide at RSUD Muyang Kute Bener Meriah, focusing on drug availability, patient information gathering, medication counseling, and labeling practices. Methods: A descriptive observational design was applied using the simulated patient method. Researchers visited the pharmacy unit with a standardized prescription scenario involving glibenclamide. Data were collected using an observation checklist immediately after each interaction. Results:The majority of pharmacy staff did not actively collect essential patient information. Counseling was limited to usage instructions, with no mention of adverse effects or drug interactions. Labels were incomplete, often missing key components such as patient name, drug name, or preparation date. However, the availability of glibenclamide remained consistent during the observation period. Conclusion: Prescription services for glibenclamide at RSUD Muyang Kute are still below optimal standards. Improvements in patient assessment, communication, and labeling practices are necessary to enhance medication safety and treatment effectiveness